A Production Strategy for Tight Gas FormationWells: Production Scheduling - IRAWAN (NIM : 22208027), HENRY
Tight gas reservoirs are classified as reservoirs which have permeability less than 0.1 mD. It is very difficult to obtain continuous production from this kind of reservoirs, without any appropriate strategy of production. This thesis presents a production strategy to achieve plateau rate condition. The strategy provides a production schedule contains opening and shut-in period. The purpose of shutting in the well is to increase reservoir pressure; therefore, the well potential will increase for the next production period. To obtain continuous rate of production from the production periods, 2 or more wells should be involved; once a well is shut in, then the other well is on production. A production schedule is compiled using 2 and 3 wells; each model has only one/single well. Using CMG simulator production performance curves could be obtained and will be applied into a production schedule in order to give a continuous constant production. This method can be applied for n models, where n is the number of model/wells. For uniform/homogenous reservoirs, a single well simulator result can be used to develop the whole production schedule that consists of multi wells, by shifting the time of production performance. For models with different characteristics of reservoir, production scheduling could be developed by using production performance (simulator results) of each well model.